A 56-Year-Old Woman with Urgency Hypertension and Suspected Heart Failure and The Risk Factor of Obesity, Sedentary Lifestyle, and Genetic - dasa novita, khuznita; Fadhelia Arta, Evelyna; Rusnianah, Farida (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2024)
A 56-year-old woman presented with the primary complaint of urgency hypertension and suspected heart failure. The patient has a history of obesity and a sedentary lifestyle, both of which are key risk factors for the development of hypertension and cardiovascular diseases. Her medical history revealed infrequent physical activity, a high-calorie diet, and a family history of hypertension and heart disease. Physical examination and supporting tests indicated markedly elevated blood pressure, signs of heart failure, and changes in the electrocardiogram suggesting possible left ventricular hypertrophy. Genetic factors, obesity, and a sedentary lifestyle played a significant role in the exacerbation of her condition. Management involving blood pressure control, heart failure therapy, and lifestyle modifications is crucial to reduce the risk of further cardiovascular complications. This article aims to discuss the relationship between obesity, sedentary behavior, genetic predisposition, and the development of hypertension and heart failure in older women. Both medical and non-medical histories were explored to determine the involved risk factors, followed by two home visits to further assess and identify additional risk factors. This case report highlights the role of the family medicine approach, where the interaction of biopsychosocial variables necessitates holistic and comprehensive therapeutic.